THE URGENCY OF CRIMINALIZING DOXING AS A CYBER CRIME IN INDONESIAN CRIMINAL LAW - Olden Siahaan; Rahmayanti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The rapid development of digital technology in Indonesia has given rise to new forms of cybercrime, including doxing—the unauthorized collection and public dissemination of personal data with the intent to intimidate, harass, or cause harm. Despite the escalating prevalence of doxing incidents, particularly targeting journalists, activists, and ordinary citizens, Indonesian criminal law does not yet contain a specific provision that explicitly criminalizes doxing as a distinct cyber offense. This study examines the urgency of criminalizing doxing within the framework of Indonesian criminal law by employing normative legal research with statutory, conceptual, and comparative approaches. The analysis evaluates the adequacy of existing legal instruments—namely Law No. 1 of 2024 on Electronic Information and Transactions (ITE Law) and Law No. 27 of 2022 on Personal Data Protection (PDP Law)—in addressing doxing. Furthermore, a comparative analysis is conducted with the legal frameworks of Hong Kong, Singapore, and the European Union. The findings reveal that current Indonesian regulations are insufficient to address the specific characteristics of doxing, creating a significant legal vacuum. The study concludes that Indonesia urgently requires explicit criminalization of doxing, supported by clear legal definitions, graduated sanctions, and robust enforcement mechanisms aligned with international human rights standards.